Strategi Bumdes dalam Meningkatkan Kesejahteraan Masyarakat di Sidokepung, Sidoarjo - Ridho Tri Winisudo; Fransiscus Xaverius Sri Sadewo (TEMALI : Jurnal Pembangunan Sosial, 2021)
BUMDes is a social entity that pays attention to the interests of community welfare by providing social services from the BUMDes institution itself. This research will discuss the strategy of BUMDes in improving the welfare of the people of Sidokepung Village. The purpose of this research is to see how the BUMDes strategy of Sidokepung Village is in carrying out their activities to launch their vision and mission for the welfare of the village community and improve the village economy with a business run by BUMDes. This study uses a qualitative descriptive approach. This research uses W.W. Rostow as a theory of development. These study results are BUMDes, namely savings and loans and selling basic foodstuffs at low prices. It is a strategy for BUMDes to increase the independent entrepreneurship of the Sidokepung Village community with this assistance. However, those who know are the lack village resource potential and community awareness. Therefore, another strategy is needed: socialization with the community to create quality human resources to innovate with minimal village resources and facts on technology to provide extensive information about the BUMDes.